An assessment of participatory governance in Mangaung Metropolitan Municipality in the Free State - Letawana, S. J. (University of the Free State, 2017)
In South Africa, the legislative mandate brought about the transition to democracy, and the subsequent policy and legislation framework, such as the Constitution of the Republic of South Africa, 1996; the White Paper on Local Government, 1998; the Local Government: Municipal Structures Act, Act 117 of 1998; and the Local Government: Municipal Systems Act, Act 32 of 2000, permitted citizens to take part in governance and policy-making. Yet, according to observation and the views of citizens in the Mangaung Metropolitan Municipally (MMM), the importance of participation as per the Constitution, as preached by the President and promoted by democrats, has yet to be translated into a lived reality at local government level. Furthermore, the service delivery protests that have taken place since 2004 are the result of poor participatory governance. In this regard, participatory governance in the development of municipal plans appears not to be realising its anticipated goals of closing the gap between government and its constituents because of a lack of consultation in the planning process and decision-making. Brynard (1996:138) states that local government is viewed as a means and a first point of contact to encourage the participation of people in the planning and policy-making process. This study involved a literature study, which included an extensive review of the relevant literature, legislation, policy documents, journal articles, books, conference papers and government reports on the purpose of local government, the developmental role of local government, as well as the requirements, purpose, roles, functions and mandate of municipal councillors, ward councillors, and ward committees. Newspaper articles were used to find examples of successful or unsuccessful participation. This study provides recommendations on how to ensure the continuation of participatory governance in MMM. In this regard, the findings and recommendations outline the parameters against which to measure the success of MMM’s participatory agenda, and to ensure that the sustainable development outcomes of the Integrated Development Plan (IDP) are met.
Keywords: Political planning -- South Africa -- Free State --Citizen participation.; Political participation -- South Africa -- Free State; Local government -- South Africa -- Free State; Dussertation (MGT (Governance and Political Transformation))--University of the Free State, [2017]